Proposta de modelo de gestão da pesquisa inovativa para programas de pós-graduação - Leite, Renato Cesar (2019)
Innovation and startup are words that represent the solutions to solve the major global problems. In general, some contitions were criated to explores economy utilizing courses and events. The innovation is a movement that: i) is aligned to knoledge Society and ii) incentivates the criative solutions to problems related to health, environment among others. The startup definition is the commercial innovation, justified by the necessity to generate jobs, principally to the students that leave Universities. The innovation and startup cause impact macroeconomic when attend the consumers necessities and/or generate new markets. In both cases, the frontiers are expanded. In Brazil, the innovative research is made mainly in graduate programs, with dissertations and thesis with potential to generate products to the Market. The graduation programs goal is to graduate the students and maintain the organizational infrastructure to this achieve the objective. To solve the dilema between the objective (evaluated by Capes) and expand the products to Society, some adaptations need to be done. This Thesis search for a solution to the question: how the make the management concerning the research programs in order to plot the Technologies directed to the market? The answer is a management model based in inovation and technology observation with i) planning; ii) coordenation and support to innovation and iii) education to the managers. The planning is the linked to the research project; the second is to executate in all develeping process and assuring the property of the Discovery. The third element is the education based on new knoledges, contacts and the supervisors, transforming the research in a successful new element.